Diiodido{2-(morpholin-4-yl)-N- 1-(2-pyridyl)ethylidene ethanamine-kappa N-3,N ',N ''}zinc - Gwaram, N.S.; Ali, Hapipah Mohd; Khaledi, H. (International Union of Crystallography, 2011)
In the title compound, [ZnI2(C13H19N3O)], the Zn-II ion is five-coordinated in a distorted square-pyramidal geometry, in which the basal plane is defined by three N atoms from the Schiff base ligand and one iodide ion. A second iodide ligand, situated in the apical position, completes the coordination geometry. In the crystal structure, C-H center dot center dot center dot O hydrogen bonds link a pair of molecules around an inversion centre into a dimer.